Simulasi sistem pompa suplai air bersih dengan kontrol berbasiskan PLC - Sudirman; I Nyoman Gede Baliarta; I Ketut Suherman; Achmad Wibolo (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
This paper discusses the simulation of control of a clean water pump system based on PLC. This simulation tool uses 3 tanks: tower tank, consumption tank and ground tank. The PLC used is the Zelio SR3PACKBD Smart Relay. The input is a stainless steel rod sensor placed in the tower tank and ground tank. The output is 2 pump motors and a solenoid valve. PLC program used Ladder diagram with ZELIO SOFT 2 programs. The test results show satisfactory results and the equipment required is very simple compared to conventional controls.